CD133+PD-L1+ cancer cells confer resistance to adoptively transferred engineered macrophage-based therapy in melanoma - Jiaojiao Xu; Zhe Li; Qinli Tong; Sihang Zhang; Jianchen Fang; Aihua Wu; Guoguang Wei; Chen Zhang; Sheng Yu; Binbin Zheng; Hongzheng Lin; Xueling Liao; et al. (Nature Communications)
Abstract Adoptive transfer of genetically or nanoparticle-engineered macrophages represents a promising cell therapy modality for treatment of solid tumor. However, the therapeutic efficacy is suboptimal without achieving a complete tumor regression, and the underlying mechanism remains elusive. Here, we discover a subpopulation of cancer cells with upregulated CD133 and programmed death-ligand 1 in mouse melanoma, resistant to the phagocytosis by the transferred macrophages. Compared to the CD133-PD-L1- cancer cells, the CD133+PD-L1+ cancer cells express higher transforming growth factor-β signaling molecules to foster a resistant tumor niche, that restricts the trafficking of the transferred macrophages by stiffened extracellular matrix, and inhibits their cell-killing capability by immunosuppressive factors. The CD133+PD-L1+ cancer cells exhibit tumorigenic potential. The CD133+PD-L1+ cells are further identified in the clinically metastatic melanoma. Hyperthermia reverses the resistance of CD133+PD-L1+ cancer cells through upregulating the ‘eat me’ signal calreticulin, significantly improving the efficacy of adoptive macrophage therapy. Our findings demonstrate the mechanism of resistance to adoptive macrophage therapy, and provide a de novo strategy to counteract the resistance.